Experimental study of the punching shear behavior of high performance steel fiber reinforced concrete slabs considering casting directions. (15th January 2017) - Nguyen, Thuc N.; Nguyen, Tung T.; Pansuk, Withit
Highlights: The presence of steel fiber increase the punching shear capacity of HPFRC slabs. Different casting positions lead to different punching shear behaviors of HPFRC slabs. Combination of fibers and reinforcement shows a negative effect on slabs behavior. Abstract: This paper presents the results of an experimental study on the punching shear behavior of high performance steel fiber reinforced concrete (HPFRC) slabs without shear reinforcement, particularly considering the effect of fiber orientation. In recent decades, high performance steel fiber reinforced concrete (HPFRC) has been a new achievement in concrete technology. Due to its superior mechanical properties, civil engineers can address the problem of punching shear of thin slabs that are currently widely used in buildings. By processing some studies, researchers have found that the strength capacity of the material before cracking and the post-cracking resistance strongly depend on the orientation of the fibers, which heavily rely on the casting direction and casting method. While most previous studies focused on the effect on the behavior of beams, this research particularly considers how the casting procedures as well as the volume content of the fiber affect the punching shear behavior of flat slabs.